When in doubt: the value of uncertainty for release success among incarcerated women. Issue 1 (2nd January 2021) - Haverkate, Danielle L.; Wright, Kevin A.
Abstract: Reentry can be complicated and daunting, yet people leaving prison tend to be overly optimistic about their capability to remain crime-free. This optimism could be good—where a hopeful mindset could be indicative of a prosocial future narrative. Or this optimism could be bad—where a naïve mindset could be indicative of a lack of preparation for the challenges ahead. Our goal is to explore the concept of perceived uncertainty for reentry success with a focus on how it may be useful in better preparing people to rejoin society. Using data from 200 women incarcerated in Arizona, we explore (1) the demographic characteristics that are associated with perceived uncertainty for reentry success and (2) the extent to which perceived uncertainty is associated with the identification of specific obstacles upon their release. Our findings suggest that most women are optimistic about their capability to stay out of prison, but that age, education, and custody level are associated with perceived uncertainty in this capability. Women with uncertainty are more likely to identify employment as a barrier that could bring them back to prison. We suggest that a focus on perceptions of uncertainty is critical for research and programming on prison reentry.